2011
DOI: 10.1371/journal.pone.0025900
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Stimulates Osteocyte Support of Osteoclast Activity by a RANKL-Dependent Pathway

Abstract: Sclerostin is a product of mature osteocytes embedded in mineralised bone and is a negative regulator of bone mass and osteoblast differentiation. While evidence suggests that sclerostin has an anti-anabolic role, the possibility also exists that sclerostin has catabolic activity. To test this we treated human primary pre-osteocyte cultures, cells we have found are exquisitely sensitive to sclerostin, or mouse osteocyte-like MLO-Y4 cells, with recombinant human sclerostin (rhSCL) and measured effects on pro-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
308
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(341 citation statements)
references
References 62 publications
(96 reference statements)
23
308
2
8
Order By: Relevance
“…Therefore, taken together with previous studies (13,14), our findings demonstrate that β-catenin activation increases OPG in all cells of the osteoblastic lineage, whereas it only increases RANKL in osteocytes that also express Sost. Our results are consistent with earlier studies demonstrating that elevated expression of Sost/sclerostin up-regulates RANKL (19,37) and increases osteoclasts (37). Expression of M-CSF is also elevated in daßcat Ot mice, consistent with our recent findings demonstrating that M-CSF is a downstream target of RANKL in osteocytes (38).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, taken together with previous studies (13,14), our findings demonstrate that β-catenin activation increases OPG in all cells of the osteoblastic lineage, whereas it only increases RANKL in osteocytes that also express Sost. Our results are consistent with earlier studies demonstrating that elevated expression of Sost/sclerostin up-regulates RANKL (19,37) and increases osteoclasts (37). Expression of M-CSF is also elevated in daßcat Ot mice, consistent with our recent findings demonstrating that M-CSF is a downstream target of RANKL in osteocytes (38).…”
Section: Discussionsupporting
confidence: 93%
“…(34) In vitro experiments using primary and established osteocyte cells have demonstrated that the Wnt inhibitor, sclerostin, stimulates RANKL expression, leading to an increase in the RANKL/OPG mRNA ratio favoring the formation of TRAP þ multinucleated cells. (68) These studies are also in agreement with our data demonstrating that the increased sclerostin expression observed early in CKD-MBD leads to a concomitant increase in RANKL expression that may drive osteoclastogenesis, which was associated with increased bone formation rates in the jck mouse.…”
Section: Discussionsupporting
confidence: 92%
“…Although we did not identify the specific cell source impacted by renal dysfunction, recent evidence has found that the osteocyte is the primary source of RANKL and its negative regulator OPG, and hence plays a major role in supporting osteoclastogenesis. (31,68) Osteocyte-specific deletion of RANKL in mice causes an osteopetrotic phenotype resulting from a significant decrease in osteoclast number and surface. (31) These data extend previous reports demonstrating that osteocyte-specific deletion of b-catenin is associated with an increase in the RANKL/OPG ratio, thereby supporting a role of this signaling pathway in balancing the expression of these opposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…54,58,59 When bone is subjected to loading, SOST expression and sclerostin levels decrease significantly, stimulating osteoblast activity and probably (through an effect on RANKL) inhibiting osteoclasts. 1,60,61 On the other hand, osteocytes have also recently been shown in vivo and in vitro to be the primary expressers of RANKL, a regulator of osteoclast differentiation and activation.…”
Section: Modeling: Evidence For and Implications In Acellular Bonementioning
confidence: 99%